Re-appraising the role of lymph node status in predicting survival in resected distal cholangiocarcinoma – A meta-analysis and systematic review. Issue 6 (June 2021) - Chin, Ken Min; Di Martino, Marcello; Syn, Nicholas; Ielpo, Benedetto; Hilal, Mohammad Abu; Goh, Brian K.P.; Koh, Ye Xin; Prieto, Mikel
Abstract: This systematic review and meta-analysis aimed to confirm the prognostic value of lymph node ratio (LNR), and determine an optimal LNR cut-off for overall survival (OS) in patients with distal cholangiocarcinoma (DCC) undergoing curative surgery. We additionally aimed to provide a consolidated review of current evidence regarding prognostic significance of positive lymph node count (PLNC) and total lymph node count (TLNC). A systematic search of PubMed, EMBASE and Cochrane Library was conducted from inception to October 2020. Studies were included into meta-analysis if there was histological diagnosis, curative surgery, restriction to DCC and relevant LNR results. Quality assessment was performed using the Newcastle Ottawa Scale. Findings for 1228 patients were pooled across 6 studies. Meta-analysis delineated a dose-effect gradient in which higher LNR cut-offs correlated with larger pooled hazard ratios: 0<LNR<0.2 (HR 1.54; 95% CI 1.08–2.20; p = 0.02), LNR>0.2 (HR 3.26; 95% CI 2.07–5.13; p < 0.00001) and LNR>0.4 (HR 3.59; 95% CI 2.31–5.58; p < 0.00001) when compared against a control group of LNR = 0. LNR of 0.2 (HR 2.12; 95% CI: 1.57–2.86; p < 0.0001) was found to be a significant and ideal cut-off for prognostication of poorer OS. A review of current literature reveals an ongoing debate regarding the comparative prognostic value of differing PLNC cut-offs (0/1/3 versus 0/1/4). TLNC of 10–13 is widely reported to be the minimum necessary to ensure improved long term outcomes. PLNC and LNR are strong prognostic factors for OS in DCC. An ideal LNR cut-off of 0.2 is most significantly associated with poorer OS. Highlights: Lymph node status has strong prognostic value in distal cholangiocarcinoma Higher lymph node ratio (LNR) cut-offs are associated with poorer survival (OS) LNR cut-off of 0.2 is significant and most ideal for prognostication of poorer OS Total lymph node count of 10–13 is necessary to ensure improved long term outcomes An optimal positive lymph node count cut-off (0/1/3 vs. 0/1/4) is an ongoing debate